The Rise of External Actors in Education : Shifting Boundaries Globally and Locally. - Lubienski, Christopher (Policy Press, 2022)
Reviewing diverse sites, including the US, Cambodia, Israel, Poland, Chile, Australia and Brazil, this book considers how schooling systems are being influenced by the rise of external actors who increasingly determine the content, delivery and governance of education.